Clinicopathological characteristics and management of colitis with anti-PD1 immunotherapy alone or in combination with ipilimumab. Issue 2 (24th November 2020) - Nahar, Kazi J; Rawson, Robert V; Ahmed, Tasnia; Tattersall, Stephen; Sandanayake, Neomal; Kiely, Christopher J; Lo, Serigne; Carlino, Matteo; Palendira, Umaimainthan; Scolyer, Richard A; Long, Georgina V; Menzies, Alexander M
Abstract : Background: Colitis is one of the common immune-related adverse events that leads to morbidity and treatment discontinuation of immunotherapy. The clinical presentation, endoscopic and histopathological features and best management of this toxicity are not well defined. Patients and methods: Patients with metastatic melanoma who received immunotherapy (programmed cell death protein 1 (PD1) antibodies, alone or in combination with a cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) antibody (PD1 +CTLA-4)) and who developed clinically significant colitis (requiring systemic corticosteroids) were identified retrospectively from two academic centers. Clinical data were collected for all patients; endoscopic and histopathological data were examined in a subset. Results: From May 2013 to May 2019, 118/1507 (7.8%) patients developed significant colitis; 80/553 (14.5%) after PD1+CTLA-4, 35/1000 (3.5%) PD1 alone, and three patients after Ipilimumab (IPI) alone. Combination therapy-induced colitis was more frequent (14.5% vs 3.5% in PD1 alone, p=<0.0001), had an earlier onset (6.3 weeks vs 25.7 weeks, p=<0.001), was more severe (grade 3/4 69% vs 31%, p=<0.001), and are more likely to require higher doses of steroids (91% vs 74%, p=0.01) than PD1 colitis. Among all patients treated with steroids (N=114), 54 (47%) responded and required no further therapy (steroid sensitive), 47 patients (41%) responded to infliximab (infliximab sensitive), and 13 (11%) were infliximab refractory and needed further immunosuppressive drugs. Infliximab-refractory patients all had onset within 4 weeks of immunotherapy commencement and were more likely to have an underlying autoimmune disease, have higher grade colitis, and require longer immunosuppression, yet had similar response and survival than other patients with colitis. Of 43 (37%) patients re-resumed treatment with PD1 monotherapy after colitis resolution, 16 (37%) of whom developed recurrent colitis. Endoscopic and histopathologic data were available for 64 patients. Most had left-sided colitis, with an increase in chronic inflammatory cells and neutrophils within the lamina propria, an increase in neutrophils in the surface epithelium, without increased lymphocytes or increased eosinophils. Infliximab-refractory colitis had a trend towards more confluent pancolitis with edema, erythema, ulceration, and absent vascularity with neutrophilic infiltration and erosion. Conclusion: Clinically significant colitis varies in presentation, response to immunosuppression, and endoscopic/histologic features depending on the immunotherapy type. Infliximab-refractory colitis occurs early, is often high grade, and has adverse endoscopic and histopathologic features